2018
DOI: 10.1371/journal.pone.0192189
|View full text |Cite|
|
Sign up to set email alerts
|

The number of measurements needed to obtain high reliability for traits related to enzymatic activities and photosynthetic compounds in soybean plants infected with Phakopsora pachyrhizi

Abstract: Asian rust affects the physiology of soybean plants and causes losses in yield. Repeatability coefficients may help breeders to know how many measurements are needed to obtain a suitable reliability for a target trait. Therefore, the objectives of this study were to determine the repeatability coefficients of 14 traits in soybean plants inoculated with Phakopsora pachyrhizi and to establish the minimum number of measurements needed to predict the breeding value with high accuracy. Experiments were performed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…It is important to highlight that the coefficient of variation (CV) over the two crop seasons were less than 10%, revealing high experimental accuracy. The CV obtained here was similar to the values reported other studies assessing physiological traits in soybean (Oliveira, de Azevedo Peixoto, et al., 2018; Oliveira, Peixoto, et al., 2018; Teodoro et al., 2019; Zobiole et al., 2010).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It is important to highlight that the coefficient of variation (CV) over the two crop seasons were less than 10%, revealing high experimental accuracy. The CV obtained here was similar to the values reported other studies assessing physiological traits in soybean (Oliveira, de Azevedo Peixoto, et al., 2018; Oliveira, Peixoto, et al., 2018; Teodoro et al., 2019; Zobiole et al., 2010).…”
Section: Resultssupporting
confidence: 91%
“…At 60 days after emergence (DAE), physiological traits were analysed using a portable photosynthesis analyser ( Infrared Gas Analyser —IRGA) model Li‐6400XT (LiCor Inc., Lincoln, Nebraska, USA). Photosynthetically active photon flux of 1,044 μmol m −2 s −1 and environment CO 2 concentrations (372 ± 10 mol m −2 s −1 ) were used, according to similar studies evaluating gas exchange in soybean crop (Oliveira, de Azevedo Peixoto, et al., 2018; Oliveira, Peixoto, et al., 2018). The physiological traits measured were as follows: net photosynthesis (A, μmmol CO 2 m −2 s −1 ), transpiration (E, mmol H 2 O m −2 s −1 ), stomatal conductance (gs, mol m −2 s −1 ) and internal CO 2 concentration (Ci, μmmol m −2 s −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The coefficients of variation (CV) less than 4% show high experimental accuracy and are lower than the values reported in the literature [30, 31, 37, 38]. After conducting the experiments in two crop seasons, it was observed that the genotype x environment interaction was not significant for all traits evaluated.…”
Section: Discussionmentioning
confidence: 67%
“…At 60 days after emergence (DAE), physiological traits were analyzed using a portable photosynthesis analyzer ( Infrared Gas Analyzer —IRGA) model Li-6400XT (LiCor Inc., Lincoln, Nebraska, USA). Photosynthetically active photon flux of 1044 μmol m -2 s -1 and environment CO 2 concentrations (372 ± 10 mol m -2 s -1 ) were used, according to similar studies evaluating gas exchange in soybean crop [30, 31]. The physiological traits measured were: net photosynthesis (A, mmol CO 2 m -2 s -1 ), transpiration (E, mmol H 2 O m -2 s -1 ), stomatal conductance (gs, mmol m -2 s -1 ), and internal CO 2 concentration (Ci, mmol m -2 s -1 ).…”
Section: Methodsmentioning
confidence: 99%
“…At 60 days after emergence (DAE), physiological traits were analysed using a portable) photosynthesis analyser (Infrared Gas Analyzer-IRGA) model Li-6400XT (LiCor Inc.). Photosynthetically active photon flux of 1,044 μmol m -2 s -1 and environment CO 2 concentrations (372 ± 10 mol m -2 s -1 ) were used, according to similar studies evaluating gas exchange in soybean crop (Oliveira, de Azevedo Peixoto, et al, 2018;. The physiological traits measured were as follows: net photosynthesis (A, µmmol CO 2 m -2 s -1 ) and transpiration (E, mmol H 2 O m -2 s -1 ).…”
Section: Physiological and Agronomic Assessmentsmentioning
confidence: 99%